Clinical application of three-dimensional transvaginal ultrasonography in the diagnosis of intrauterine adhesions - Xinkui Jiang (SAGE Publishing, 2021)
Objective The present study aimed to evaluate the diagnostic accuracy of three-dimensional transvaginal ultrasonography (3D-TVS) for intrauterine adhesions (IUA). Methods We performed a retrospective cohort study. A total of 500 women aged 19 to 46 years with uterine lesions who received treatment from the Department of Obstetrics and Gynecology were enrolled. Endometrial 3D imaging was conducted to obtain the display plane and 3D-TVS parameters. Patients also underwent hysteroscopy for a definitive diagnosis. Results For diagnosing IUA, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy of 3D-TVS were 98.8%, 90.8%, 91.4%, 98.7%, and 94.8%, respectively. For diagnosing a submucosal myoma, the sensitivity, specificity, PPV, NPV, and overall accuracy of 3D-TVS were 88.2%, 97.9%, 88.2%, 97.9%, and 96.4%, respectively. For diagnosing endometrial polyps, the sensitivity, specificity, PPV, NPV, and overall accuracy of 3D-TVS were 94.7%, 96.8%, 92.9%, 97.7%, and 96.2%, respectively. Conclusions Before hysteroscopy, 3D-TVS, as a method of screening, has great value for comparing differences before and after treatment, and for evaluating therapeutic effects.